STRENGTHENING THE DIGITAL ECONOMY ECOSYSTEM IN SOCIETY: A LITERATURE REVIEW AS A FOUNDATION FOR DEVELOPMENTSTRATEGIES - Amândio de Araújo Sarmento; Mokhamad Eldon; Loso Judijanto; Al-Amin (Adiba Aisha Amira, 2023)
A healthy and resilient digital economy ecosystem is essential for Indonesia to thrive in the digital age. Many studies have shown the importance of improving digital infrastructure, making progressive policies, training tech-savvy human resources, and collaboration between sectors to spur innovation. Advanced infrastructure such as fast networks and secure data centres are needed to support peak technology adoption. Good and fair rules and policies, especially on cybersecurity and data privacy, are necessary for an innovative climate and public trust. Relevant education and training are needed to ensure the availability of skilled digital labour. Cooperation between the government, the business world, the education world, and the technology community can accelerate growth and new breakthroughs in the digital economy ecosystem. By implementing these various strategies, it is hoped that the digital economy ecosystem can be improved and become the main motor for inclusive and sustainable economic growth.